Reinforcement Learning Aqidah Akhlak Sebagai Upaya Preventif Perilaku Bullying Siswa di Madrasah Ibtidaiyah Nahdlatul Ulama Darul Huda - Himmatun Nadhifah F, Dwi; Marzuki, Ahmad; Yusuf, Achmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Bullying behavior is still a problem that is often found in the Madrasah Ibtidaiyah environment, especially in the form of verbal bullying such as teasing, giving nicknames, and calling parents names, as well as nonverbal bullying such as disturbing friends during learning. This condition shows the importance of preventive efforts through learning oriented towards character building. This study aims to describe the application of reinforcement learning in Aqidah Akhlak learning and analyze its implications in preventing student bullying behavior at MI NU Darul Huda. This study uses a qualitative approach with a case study type. The research subjects include Aqidah Akhlak teachers, madrasah principals, homeroom teachers, and fifth grade students. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used the interactive model of Miles and Huberman through the stages of data reduction, data presentation, and drawing conclusions. The validity of the data was tested through triangulation of sources, techniques, and time. The results of the study indicate that the application of reinforcement learning is carried out in an integrated manner in Aqidah Akhlak learning, especially on the material of patience, discipline, independence, and repentance, through the provision of positive reinforcement in the form of praise, appreciation, and awards, as well as negative reinforcement in the form of reprimands, advice, and coaching. The implications of this implementation are evident in a decrease in verbal and nonverbal bullying behavior, an increase in mutual respect, a growing awareness of apologizing, and the development of discipline and good manners among students. Thus, reinforcement learning in Aqidah Akhlak learning is effective as a preventive strategy in preventing bullying behavior and developing students' akhlakul karimah character in madrasah ibtidaiyah